Is rheumatoid arthritis a risk factor for acute coronary syndrome also among individuals at elevated risk, such as individuals presenting with acute chest pain?. Issue 3 (26th November 2020) - Svensson, Per; Bergstrom, Miriam; Discacciati, Andrea; Ljung, Lina; Jernberg, Tomas; Frick, Mats; Linder, Rickard; Askling, Johan
Abstract : Background: Patients with rheumatoid arthritis (RA) are, on average, at increased risk of acute coronary syndrome (ACS) compared to the general population, but it remains unknown whether RA remains an ACS risk factor also in settings where the ACS risk is already high elevated, such as among individuals presenting to the emergency department (ED) with chest pain. Methods and results: We included 49 283 individuals (514 (1.0%) had RA) presenting with chest pain at the four hospital EDs in Stockholm, Sweden, 2013–2016 in a cohort study. Information on exposure (RA), outcome (ACS) and comorbidities was provided through national registers. The association between RA and ACS was assessed, overall and by levels of high-sensitivity cardiac troponin T (hs-cTnT) and number of ACS risk factors, using logistic regression models adjusted for age, sex, hospital, calendar year and cardiovascular risk factors. ACS was more common in patients with (8.2%) than without (4.6%) RA, adjusted OR =1.4, 95% CI 1.0 to 2.0. This association was particularly strong in individuals with initial hs-cTnT levels between 5 and 14 ng/L, or no additional ACS risk factors (adjusted ORs above 2), but no longer detectable in those with hs-cTnT >14 ng/L or with three or more additional ACS risk factors. Conclusion: RA is a risk factor for ACS also among patients at the ED with chest pain. This association is not explained by traditional ACS risk factors, and most pronounced in patients with normal hs-cTnT and few other ACS risk factors, prompting particular ACS vigilance in this RA patient group.